2018
DOI: 10.1007/s12603-017-0897-0
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal Support, Dysphagia, Malnutrition, and Activities of Daily Living in Aged Individuals Needing Long-Term Care: A Path Analysis

Abstract: In aged individuals needing long-term care, occlusal support is associated directly with dysphagia and indirectly with malnutrition and activities of daily living via dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
1
21
0
6
Order By: Relevance
“…However, rehabilitation and nutritional interventions alone are not sufficient, and oral and dental approaches might also be important. 30 There were several potential limitations to the present study. First, despite adjusting for many potential confounders, because of the retrospective nature of the study we could not adjust for some potential confounding factors related to sarcopenia, OHRQoL and oral health status, such as depression.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, rehabilitation and nutritional interventions alone are not sufficient, and oral and dental approaches might also be important. 30 There were several potential limitations to the present study. First, despite adjusting for many potential confounders, because of the retrospective nature of the study we could not adjust for some potential confounding factors related to sarcopenia, OHRQoL and oral health status, such as depression.…”
Section: Discussionmentioning
confidence: 87%
“…For the prevention and treatment of sarcopenia, a treatment known as rehabilitation nutrition, combining both rehabilitative training and nutrition management, is required. However, rehabilitation and nutritional interventions alone are not sufficient, and oral and dental approaches might also be important …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the relative short time required to perform the whole CGA, all these tests, including dysphagia, can be easily performed and adapted in all Geriatric Labs. To our knowledge, no specific relationship has been described between dysphagia and SPPB in aged population, but some studies showed a significant association between dysphagia and frailty measurements [22,32,36], or activities of daily living (ADL) [23].…”
Section: Tablementioning
confidence: 99%
“…Although studies support that dentures can reduce the complications of tooth loss [18,19], it also promotes some problems such as the high risk of candida, denture stomatitis [20,21] and pneumonia [22,23], especially if the dental plates are not kept clean, which should be considered.…”
Section: Tooth Loss and Dysphagiamentioning
confidence: 99%